Tri-Nodal Social Entanglements in Iron Age Sicily: Material and Social Transformation - (:unkn) unknown (My University, 2020)
Indigenous Iron Age Sicilian populations underwent a series of complex social transformations following the establishment of neighboring Greek and Phoenician trade posts in the eighth through fifth centuries BC. This paper employs the theory of cultural hybridity to explore indigenous Iron Age Elymian responses to the socially entangled atmosphere. Prolonged contact and interaction with foreigners fostered numerous alterations to Elymian pottery, architecture, and language. Such archaeologically visible changes are discussed, accounting for the development of a complex social middle ground encompassing the Elymi, Greeks, and Phoenicians. Additionally, this paper offers an agenda for future research focusing on the development of mixed-style material culture within complex social entanglements.
Keywords: Cultural Hybridity; Sicily; Elymi; Iron Age; Social Transformation